Survival of Hepatitis C Virus in Syringes Is Dependent on the Design of the Syringe-Needle and Dead Space Volume. - Binka, Mawuena; Paintsil, Elijah; Patel, Amisha; Lindenbach, Brett D; Heimer, Robert (PloS one, 2015)
Many people who inject drugs (PWID) use syringes with detachable needles, which have high dead space (HDS). Contaminated HDS blood may substantially contribute to the transmission of HIV, hepatitis C (HCV), and other blood-borne viruses within this population. Newly designed low dead space (LDS) syringe-needle combinations seek to reduce blood-borne virus transmission among PWID. We evaluated the infectivity of HCV-contaminated residual volumes recovered from two LDS syringe-needle combinations.